Pengaruh Shopee Live dan Fitur Spay Later terhadap Perilaku Konsumtif Remaja - Nafhan, Nafisah; Apriadi, Deri (UNIVERSITAS MARITIM AMNI SEMARANG, 2025)
This study aims to analyze the effect of Shopee Live and Shopee PayLater on the consumptive behavior of teenagers in Bandung. A quantitative approach was employed using a survey method with 75 respondents aged 13–24 years who had experience with both features. Data were collected using a five-point Likert scale questionnaire and analyzed through multiple linear regression with the aid of SPSS version 26. Validity and reliability tests confirmed that all questionnaire items were valid and reliable, while classical assumption tests indicated that the regression model met the criteria of normality, multicollinearity, and heteroscedasticity. The regression results revealed that Shopee Live had a positive and significant influence on teenagers’ consumptive behavior, whereas Shopee PayLater showed no significant effect when tested partially. However, when examined simultaneously, both features significantly affected consumptive behavior. These findings highlight that interactive promotions through Shopee Live play a more dominant role in shaping teenagers’ consumptive behavior compared to financial access via Shopee PayLater.